(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This paper explores contemporary methods of language learning, emphasizing the integration of digital technologies and interactive approaches. It examines how these methods enhance flexibility, personalization, and engagement in the learning process. The study highlights the effectiveness of various digital platforms and traditional strategies, such as movies, podcasts, and gamification, in promoting language acquisition. By analyzing the benefits and challenges of modern learning techniques, this paper aims to provide insights into creating a more efficient and enjoyable language learning experience. Ultimately, the findings suggest that a combination of digital and traditional methods can significantly improve learners’ proficiency and cultural understanding.